Modeling Biological Systems in Stochastic Concurrent Constraint Programming - Bortolussi, Luca; Policriti, Alberto (Constraints : an international journal, 2008)
We present an application of stochastic Concurrent Constraint Programming (sCCP) for modeling biological systems. We provide a library of sCCP processes that can be used to describe straightforwardly biological networks. In the meanwhile, we show that sCCP proves to be a general and extensible framework, allowing to describe a wide class of dynamical behaviours and kinetic laws.